Gender and unruly titles in the booklists of the Gelasian Decree - Solevåg, Anna Rebecca (Journal for the study of the pseudepigrapha, 2023)
This essay offers a new perspective on the booklists of the Gelasian Decree (Decretum Gelasianium) from the sixth century. In this document’s apocryphal booklist, there are several titles featuring female or feminine names that exhibit a certain unruliness. Whether known only by title or by many titles, these entries pose the question of why female figures and texts not usually associated with heresy are constructed under this rubric in the Gelasian Decree. By untangling the lists from the academic discourse on canon and rather understanding them in the context of the document as a whole, the essay offers a fresh reading of the relations between gender, apocryphal books, and church hierarchy. Through an analysis of the occurrences of female/feminine names and signifiers throughout the text, it is found that while male figures are associated with God, the church hierarchy, and canonical and legitimate literature, the categories of apocrypha and heresy are feminized. It is argued that the “unruly” book titles in the Gelasian Degree ultimately resist the organizing efforts of its author.